Understanding consumption experiences: a discourse analysis of travel blogs - Bosangit, Carmela (2012)
Blogging has captured the attention of the public as a platform for self-presentation and self expression; social interaction (Guadagno, Okdie and Eno, 2007; Schmidt, 2007), and as a source of information (Schmidt, 2007). Blogs provided self-reflexive consumers with a platform to describe their own action in their own words (Caru and Cova, 2006); hence offer new spaces for the study of unleashed consumers’ narratives (Schau and Gilly, 2003; Kozinets et al 2010 and Pace, 2008). This presents opportunities for addressing research gaps in the literature of consumption and tourist experiences. Travel blogs as rich narratives of travel experiences can provide an emic perspective of what constitutes the bloggers’ experience and provides in-depth insights on measuring the outcome of this subjective and personal experience. The discourse analysis of travel blogs is a novel approach to understanding tourist experiences through their reconstruction of their stories to their readers. The analysis of travel blogs reveals elements that constitute core experiences that have, to date, proved to be elusive to marketers. The thesis also contributes to the understanding of this new blogging phenomenon among travellers that has become part of their tourist experiences. Marketing and managerial implications of the key findings of the discourse analysis of travel blogs and the survey on travel bloggers are provided in the thesis. The thesis responds to the urgency of understanding the concept of experience, as intensified by the emergence of the experience economy where “experience” is seen as having a higher economic value compared to goods and services.